Propagation of uncertainty from observing systems and NWP into hydrological models: COST‐731 Working Group 2 - Zappa, Massimiliano; Beven, Keith J.; Bruen, Michael; Cofiño, Antonio S.; Kok, Kees; Martin, Eric; Nurmi, Pertti; Orfila, Bartlomé; Roulin, Emmanuel; Schröter, Kai; Seed, Alan; Szturc, Jan; et al. (Atmospheric Science Letters, 2010)
Abstract The COST‐731 action is focused on uncertainty propagation in hydrometeorologica l forecasting chains. Goals and activities of the action Working Group 2 are presented. Five foci for discussion and research have been identified: (1) understand uncertainties, (2) exploring, designing and comparing methodologies for the use of uncertainty in hydrological models, (3) providing feedback on sensitivity to data and forecast providers, (4) transferring methodologies among the different communities involved and (5) setting up test‐beds and perform proof‐of‐concepts. Current examples of different perspectives on uncertainty propagation are presented. Copyright © 2010 Royal Meteorological Society
Keywords: Ouvrage_Collectif_Numéro1

River flood plains are model ecosystems to test general hydrogeomorphic and ecological concepts - Tockner, Klement; Lorang, Mark S.; Stanford, Jack A. (River Research and Applications, 2010)
Abstract A major challenge in ecology is to link patterns and processes across different spatial and temporal scales. Flood plains are ideal model ecosystems to study (i) the processes that create and maintain environmental heterogeneity and (ii) to quantify the effects of environmental heterogeneity on ecosystem functioning and biodiversity. Fluvial processes of cut‐and‐fill alluviation create new channels, bars and benches within a flood plain that in turn provides new surface for subsequent vegetative recruitment and growth resulting in a shifting mosaic of interconnected aquatic and terrestrial habitat patches. Composition and spatial arrangement of these habitat patches control the movement of organisms and matter among adjacent patches; and the capacity of a habitat to process matter depends on the productivity of adjacent patches and on the exchange among these patches. The exchange of matter and organisms among habitats of different age and productivity is often pulsed in nature. Small pulses of a physical driver (e.g. short‐term increase in flow) can leach large amounts of nutrients thereby stimulating primary production in adjacent aquatic patches, or trigger mass emergence of aquatic insects that may in turn impact recipient terrestrial communities. Hence, biodiversity in a river corridor context is hierarchically structured and strongly linked to the dynamic biophysical processes and feedback mechanisms that drive these chronosequences over broad time and space scales. Today, the active conversion of degraded ecosystems back to a more heterogeneous and dynamic state has become an important aspect of restoration and management where maintaining or allowing a return to the shifting habitat mosaic dynamism is the goal with the expected outcome greater biodiversity and clean water among other valuable ecosystem goods and services. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

Inundation extent as a key parameter for assessing the magnitude and return period of flooding events in southern Iceland - Pagneux, Emmanuel; Gísladóttir, Guðrún; Snorrason, Árni (Hydrological Sciences Journal, 2010)
Keywords: Ouvrage_Collectif_Numéro1

Health and social impacts of a flood disaster: responding to needs and implications for practice - Carroll, Bob; Balogh, Ruth; Morbey, Hazel; Araoz, Gonzalo (Disasters, 2010)
Carlisle in northwest England suffered its worse floods for more than 180 years in 2005. A study, reported here, was undertaken to assess the health and social impacts of these floods via in‐depth, taped individual and focus‐group interviews with people whose homes had been flooded and with agency workers who helped them. Respondents spoke of physical health ailments, psychological stress, water health‐and‐safety issues related to the floods, and disputes with insurance and construction companies, which they felt had caused and exacerbated psychological health problems. Support workers also suffered from psychological stress. Furthermore, it was found that people had low expectations of a flood and were not prepared. The findings are presented in five sections covering flood risk awareness, water contamination issues, physical health, mental health, and impact on frontline support workers. The discussion focuses on the implications of the findings for policy and practice vis‐à‐vis psychological health provision, contamination issues, training and support for frontline support workers, matters relating to restoration, and preparation for flooding.